Community Economic Empowerment With The Tabulampot Method In Medan Sinembah Village, Deli Serdang, North Sumatra - Hutasuhut, Julianto; Rasyid Syamsuri, Abd.; Falahi, Adrial; Yuliana, Yayuk (CV. Inara, 2022)
This community service was conducted in Medan Sinembah Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province. Based on the the research results, information was obtained that in general the community faces several problems regarding economic empowerment, one of which is their lack of ability from the aspect of science and technology to make their home gardens more productively. The purpose of this community service is to provide direction and socialization for the community through women from Family Welfare Empowerment regarding vegetable cultivation using the Tabulampot method (Planting Fruits in Pots) so that they are more motivated and proactive to solve the economic problems they are facing. The benefits that are expected from this community service activity are the people can use the land around their home yards for more productive results and at the same time can make it a valuable experience in entrepreneurship. At least vegetable cultivation using the tabulampot method, a group of families can save household costs by no longer buying vegetables to meet their daily needs. The methods used in this activity are as follows: (1) Focus Group Discussion (FGD), (2) Lecture method, and (3) Demonstration method. The expected outcome of this community service is an increase in the knowledge and technology possessed by the community about vegetable cultivation using the tabulampot method.